2015
DOI: 10.1089/hum.2015.001
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Recombinant Adeno-Associated Virus-Mediated Expression for Large Transgenes, Using a Synthetic Promoter and Tandem Array Enhancers

Abstract: The packaging capacity of recombinant adeno-associated viral (rAAV) vectors limits the size of the promoter that can be used to express the 4.43-kb cystic fibrosis transmembrane conductance regulator (CFTR) cDNA. To circumvent this limitation, we screened a set of 100-mer synthetic enhancer elements, composed of ten 10-bp repeats, for their ability to augment CFTR transgene expression from a short 83-bp synthetic promoter in the context of an rAAV vector designed for use in the cystic fibrosis (CF) ferret mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 56 publications
0
55
0
Order By: Relevance
“…This vector genome contains a CFTR minigene (CFTRΔR contains a 156-bp partial deletion at the R-domain; refs. 17, 25) under the direction of a short 183-bp synthetic enhancer/promoter (F5Tg83) that has been shown to express efficiently in CF humanairway epithelia and restore CFTR channel activity (26). Using this vector genome packaged into the AAV2H22 capsid, analysis of short-circuit current in Ussing chambers demonstrated that AAV2H22-CF-TRΔR rescues cAMP-stimulated Cl − current (Isc cAMP ) in CF pig airway epithelia (Figure 1E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This vector genome contains a CFTR minigene (CFTRΔR contains a 156-bp partial deletion at the R-domain; refs. 17, 25) under the direction of a short 183-bp synthetic enhancer/promoter (F5Tg83) that has been shown to express efficiently in CF humanairway epithelia and restore CFTR channel activity (26). Using this vector genome packaged into the AAV2H22 capsid, analysis of short-circuit current in Ussing chambers demonstrated that AAV2H22-CF-TRΔR rescues cAMP-stimulated Cl − current (Isc cAMP ) in CF pig airway epithelia (Figure 1E).…”
Section: Resultsmentioning
confidence: 99%
“…A 4.88 kb recombinant AAV2 (rAAV2) genome, which expresses CFTRΔR under the control of a short synthetic enhancer/promoter F5tg83 and synthetic polyadenylation signal vector (26), was packaged into the AAV2H22 capsid to produce the AAV2H22-CFTRΔR. The replication-competent AAV (rcAAV) library and rAAV vectors were packaged and purified via iodixanol gradient centrifugation as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…These researchers noted partial restoration of chloride transport that was similar to the restoration that occurred when they used an adenovirus containing wt CFTR for transduction. As mentioned in the previous section, Yan and colleagues 50 have created AV2/2.F5tg83-CFTRΔR and shown that transfection with this construct restores function to human CF bronchial epithelial cells. These two different strategies, the use of transcomplementation and a Cl − channel missing part of the R domain of CFTR, seem to have solved the problem of how to truncate CFTR to fit the packaging limit of AAV and still restore function to cells containing mutations in CFTR.…”
Section: Truncating Cftrmentioning
confidence: 98%
“…To boost the expression even further, they identified a 100-bp enhancer (F5) from a screen of over 52,000 unique oligonucleotide sequences and created a new vector, AV2/2.F5tg83. The vector with the enhancer (AV2/2.F5tg83) showed a 17-fold increase in the expression of CFTR and an improvement in CFTR-generated Cl − currents of ~19-fold in CF human epithelial cell cultures grown in air-liquid cultures when compared to the AV2/2.tg83 vector without the enhancer 50 . From these studies it is clear that new promoters can drastically improve the expression and function of CFTR to well above that which could be achieved with the older-generation tgAAV2-CFTR vector.…”
Section: New Promotersmentioning
confidence: 99%
“…AAV vectors have thus been produced by transfection of three separate plasmids each containing one of these attributes: ITRs flanking the therapeutic gene cassette, rep/ cap genes or essential helper genes [50,51]. AAV has been shown to induce long-term transgene expression in a variety of tissues; thus, it has been actively explored for the treatment of genetic and acquired diseases, such as cystic fibrosis, hemophilia, Parkinson's disease and muscular dystrophy [52][53][54][55]. Although AAV-mediated gene therapy is efficient in tissues of varying origin, the most efficient transduction has been reported in skeletal muscle in vivo [52,56].…”
Section: Adeno-associated Virusmentioning
confidence: 99%